An empirical study on customer preference towards online shopping among engineering students in a private university in Vellore District, Tamil Nadu, India. (2016) - Vasumathi, A.; Rekha, K. Sasi; Subashini, R.
The younger generations are now becoming most valuable consumers in the global market and they play an important role in an online shopping. In the past decades, most of the business organisations depend and ran their business with the newer technology particularly focusing on younger generation. The increasing use of internet by the younger generation such as engineering students provides an emerging prospect for online retailers. Based upon this, an empirical study was conducted and the researchers have collected data from 100 engineering students of a private university in Vellore by distributing a well structured questionnaire. The researchers found that the students' spent pocket money in online shopping was less than Rs. 5, 000 compared to other respondents' with different slab of pocket money. The researchers found that the number of years of using internet is an important independent variable in predicting the preference towards online purchasing.